Implementasi Kurikulum Al-Islam dan Kemuhammadiyahan (AIK) Melalui Model Student Centered Learning (SCL) di Program Studi Pendidikan Dokter Fakultas Kedokteran dan Kesehatan Universitas Muhammadiyah Jakarta - Andriyani, Andriyani; Nata, Abuddin; Saefuddin, Didin (Ta'dibuna: Jurnal Pendidikan Islam, 2014)
The course of AIK on Medical Education Department (MED) from the Faculty of Medicine and Health at the University of Muhammadiyah Jakarta, has the great vision to prepare the students to become Muslim community that implement the pure Islamic teaching in all aspects of life. At the same time, the implementation of AIK in MED is designed with curriculum blocks with Student Centered Learning (SCL) learning model, and this has not become university policy yet. This study will evaluate whether the curriculum blocks with Student Centered Learning (SCL) for AIK can achieve Muhammadiyah mission or not. Issues to be addressed in this study were 1 ) whether the curriculum developed with the block system capable of promoting the students to be scholars in accordance with the aspired Muhammadiyah, 2 ) whether the Student Centered Learning (SCL) model learning can enhance the understanding of Islam, developing behaviour to be a true Muslim and implementing social interaction in inclusive ways, pluralist and respect for diversity, and 3) whether the management of the campus contributes to the effectiveness of learning and controls the culture of the campus. The research methods were mixture of qualitative and quantitative. The main design is qualitative, so, the conclusions are formulated based on the facts and results of the study. A qualitative approach was also used to obtain information on the implementation of curriculum AIK block 2 by learning on Student Centered Learning (SCL) ways, and the technique was interview. While quantitative was used to take measurements of the response of the student and their learning experience of AIK learning programs. The sample of this research were the students MED academic year 2011/2012 and following AIK block 2, which have been completed AIK 1, all the informations were got by the questionnaire. The research results that implementation of SCL model in learning al-Islam and Kemuhammadiyahan by block system amongst Medical Education Program Faculty of Medicine and Health, University of Muhammadiyah Jakarta, based on the data and analysis of qualitative and quantitative data can be concluded there is a strong synergy between the content of curriculum with Islamic personality development blueprint aspired by Muhammadiyah, in five spirits of reforms purification of belief and worship on God, management system of the organisation , preparing cadres, ethics reform and renewal of leadership. Then, AIK with Student Centered Learning (SCL) models have also been able to deliver the student into the community Muhammadiyah who have a better understanding of the Muhammadiyah teachings, religion, have the idealism to be a smart Muslim society, competitive, innovative and able to build unity, pluralism and inclusiveness. This success is not only the result of learning with the block curriculum, and learning models of Student Centered Learning (SCL) but also by intervene from the faculty management in controlling the campus environment to be supporting for the needs of the achievement of objectives and the implementation of learning process. Recommendation, Learning AIK on the model of block curriculum and learning by SCL model need to be expanded implementation across faculties in UMJ, because the implementation of such model has been producing better understanding of Muhammadiyah doctrine, changes in behaviour, attitude and a very positive outlook towards attaining Muhammadiyah society. Then, for the success of learning AIK with block systems and Student Centered Learning (SCL) models, UMJ must prepare a good learning resources, library, internet and teaching materials and module of the lecturers. Then, UMJ also must provide policies campus culture that supports successful of AIK. Keywords: Curriculum Block, Student Centred Learning, al-Islam and Muhammadiyah